Enhancing Students’ Future Problem-solving Skills for Educational Internship Preparation - Yusmawati, Yusmawati; Rohman, Moh. Fathur; Abidin, Dindin; Asmawi, Moch. (Journal of Technical Education and Training, 2024)
The goal of this study was to assess the future problem-solving skills of students as they prepare for an educational internship program. The research used an experimental design and involved five universities in Indonesia. There were a total of 10 class groups, with five acting as control groups and five as experimental groups. The study included 300 students and five prerequisite course lecturers, and a random sampling technique was employed. Three instruments—a problem-solving test, a future problem-solving test, and a standardized achievement test—were administered to all participating students. The results indicated that the design of educational internship prerequisite courses with a future problem-solving approach significantly impacted students' ability to come up with original problems. However, it did not improve the contextuality, complexity, and diversity of issues proposed. The study focused on designing, implementing, and evaluating prerequisite courses for educational internships to improve problem-solving skills, future problem-solving skills, student beliefs about the physical education and health teaching profession, and attitudes toward posing academic problems as future educators. Additionally, the study developed a framework for teaching and assessing problem submission.